Systematics, biogeography, and evolution of Pristurus minimus (Squamata, Sphaerodactylidae) with the discovery of the smallest Arabian vertebrate. Issue 4 (19th May 2019) - Tamar, Karin; Mitsi, Pelagia; SimÓ-Riudalbas, Marc; Tejero-Cicuéndez, Héctor; Al-Sariri, Thuraya; Carranza, Salvador
Abstract : Almost 20% of Oman's terrestrial reptiles are found on Masirah Island. Despite its ancient geological history and its long isolation, Masirah Island only harbours one endemic reptile species, Hemidactylus masirahensis . In this study, we use an integrative approach to explore the variation in Pristurus minimus, to revise its systematics and to assess its phylogeography by using molecular (mitochondrial and nuclear DNA sequences) and morphological data. Our results uncovered a deep divergence within P. minimus that dates back to ∼4 Ma, during the Pliocene Epoch. The old divergence separated P. minimus into two allopatric species: one from mainland Arabia, P. minimus, and one endemic to Masirah Island, described as a new species herein. Despite the general similarity between the two sister species, there are morphological differences related mainly to body size. The new Pristurus species endemic to Masirah Island is significantly smaller than its mainland sister taxon, becoming the smallest known vertebrate species in Arabia and one of the smallest lizard species in the world. The phylogenetic analyses also uncovered a low level of genetic diversity within the newly described Pristurus species endemic to Masirah Island and a relatively deep genetic divergence within P. minimus that dates back to the Pleistocene. Once more, the present study highlights the relatively high levels of reptile diversity and endemicity in south-eastern Arabia despite its harsh, arid climate and stresses its relevance from a conservation point of view. The LSIDs for this publication is: urn:lsid:zoobank.org:pub:DB0658D5-7F68-4E66-885F-75E27F9CD512 .